Human Resource Practices for Corporate Social Responsibility: Evidence From Korean Firms - Bang, Se-Rin; Choi, Myeong-Cheol; Ahn, Ji-Young (Frontiers in Psychology, 2022)
Human resource management (HRM) in managing environmental, social, governance (ESG) or corporate social responsibility (CSR) initiatives have been recently raised, yet little attention has been paid to integrating CSR and HRM. Our primary goal was to identify how and whether certain HR practices are critical for developing employee capability to operate in firms with active CSR initiatives. We first examine the impact of external CSR activities on firm-level work outcomes. Moreover, we attempt to identify a choice of particular HR practices that could be aligned with external CSR activities. We then empirically examine how each HR practice interacts with external CSR activities that influence employee retention and labor productivity. Using three longitudinal datasets conducted by the government-sponsored research institution over 154 publicly-traded Korean firms for five waves of survey years, the results show that external CSR has a limited impact on employee retention and labor productivity. However, when external CSR activities are combined with a specific set of HR practices, including person-organization fit-based selection, performance-based pay, extensive investment of training and development, and employee suggestion program, the impact of external CSR on employee work outcomes is more substantial. The results indicate that external CSR and a particular set of HR practices as internal CSR can be complementary and generate a positive interaction on creating sustainable human capabilities.